A comparative evaluation of students' specialist's and bachelor's degrees development indicators - Albert A. Abrosimov; Vyacheslav V. Zayvyy (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The purpose of this study is to assess the effectiveness of the educational process in the transition to the level system of higher education in comparison with the specialty system.During the transition to the level system of education, the curriculum, a set of disciplines and the correlation between different types of educational activity in almost every discipline have significantly changed.Comparative evaluation of the effectiveness of training in the specialty system and the level system for those disciplines that have passed from the specialty system and the level system, is able to assess the indicated transition, limited only by these disciplines. Therefore, the parameters of comparison are indicators of the development of students who have been trained in the specialty system and students studying in the level system. The studies were carried out on the basis of experimental data obtained by testing undergraduate students and specialty students.For detailed analysis, the separation of each of the two complete samples into approximate statistical intervals in which the comparison is being made.For the estimation in each statistical interval, differences in the average values of the accepted development indices and differences in the profiles of development indices within the samples and between the samples are analyzed. The most significant differences in the level of development of undergraduate and specialty students are revealed in the statistical interval "Normal", in which undergraduate students are inferior to specialty students in eight out of ten indicators. In the statistical intervals "More than normal" and "Less than the normal", undergraduate students in general are slightly inferior to specialty students. The study presents the comparison results for each accepted development indicator.Reduction in the development level of undergraduate students in comparison with specialty students can be the result of several factors. At present, the reason of the decrease is not possible to be indicated.